Assessment of Acute Rejection by Global Longitudinal Strain and Cardiac Biomarkers in Heart-Transplanted Patients - Clemmensen, Tor Skibsted; Firooznia, Nilufar; Olawi, Fariha Morsal; Løgstrup, Brian Bridal; Poulsen, Steen Hvitfeldt; Eiskjær, Hans (Frontiers in Immunology, 2022)
Aims The aim of this study was to evaluate left ventricular global longitudinal strain (LVGLS), N-terminal pro brain natriuretic peptide (Nt-ProBNP), and Troponin T as non-invasive markers for acute cellular rejection (ACR) diagnosis and severity assessment after heart transplantation (HTx). Methods We retrospectively included all HTx patients transplanted from 2013 to 2019. At each visit, the patients were subjected to endomyocardial biopsy (EMB), measurement of Nt-ProBNP and Troponin T, and protocoled echocardiography with assessment of LVGLS. Sudden drop in graft function (SDGF) was defined as a drop in LVGLS ≥-2% in combination with either an increase in Troponin T ≥20% or Nt-ProBNP ≥30% compared with levels at the latest visit. Results We included 1,436 EMBs from 83 HTx patients. The biopsies were grouped as 0R (n = 857), 1R (n = 538), and ≥2R (n = 41). LVGLS was lower and Troponin T and Nt-ProBNP higher in the 2R group than in the 0R and 1R groups (LVGLS: -12.9 ± 3.8% versus -16.9 ± 3.1% and -16.1 ± 3.3%; Troponin T: 79 [33;230] ng/l versus 27 [13;77] ng/l and 27 [14;68] ng/l; Nt-ProBNP: 4,174 [1,095;9,510] ng/l versus 734 [309;2,210] ng/l and 725 [305;2,082], all p < 0.01). A SDGF was seen at 45 visits of which 19 had ≥2R ACR. EMBs showed ACR in 20 cases without SDGF. Finally, neither was SDGF seen nor did the EMB show rejection in 1,136 cases. Thus, the sensitivity of SDGF for ≥2R ACR detection was 49% (32–65) and specificity 98% (97–99). The positive predictive value (PPV) was 42% (31–55) and the negative predictive value (NPV) 98% (98–99). The diagnostic value improved in a sub-analysis excluding EMBs within 3 months after HTx, clinically interpreted false positive ≥2R ACR cases, and cases with ≥2R ACR who recently (<2 weeks) were treated with intravenous methylprednisolone due to ≥2R ACR (sensitivity 75% (48–93), specificity 97% (96–98), NPV 99% (99–100), and PPV 39% (27–52). Conclusions Patients with ≥2R ACR have lower LVGLS and higher Troponin T and Nt-ProBNP than patients without 2R rejection. A non-invasive model combining changes in LVGLS and Troponin T or Nt-ProBNP showed excellent negative predictive value and moderate sensitivity and may be used as a gatekeeper to invasive biopsies after HTx.